Menggali Potensi Penciptaan Brand dan Desain Kemasan Makanan UNRIYO - Wulandari, Novi; Rahmayanti, Dian Rhesa; Rohmah, Khaula Lutfiati; Metty, Metty; Nugroho, Setyo Mahanani (Jurnal Pengabdian Dharma Bakti, 2020)
Today,there are many universities that carry out the princip leofentrepreneurship within their vision and mission, and so does Respati Yogyakarta University (UNRIYO). If most universities have started independent business units both inside and outside their institutions, it can be said that UNRIYO is still far behind. To begin to realize a dream to have an independent business unit within the institution, the RECENT team has a simple idea but it is likely to bring tremendous benefits, namely the creation of a brand and design for the UNRIYO catering tools, namelythesnackbox and the lunch box.Dueto the lack of Human Resources(HR) in the RECENT team and very limited initial capital, we think that this business is the most possible one to do. Talking about brands, it cannot be separated from the discussion about branding. If the brand word refers to a brand, then the definition of branding is a variety of communication activities carried out by accompany with the aimof building and raising abrand. These two things are the main activities of our program this time. In addition, by carrying out a brand and doing branding on UNRIYO catering tools, we have a mission to instil a positive image so as to foster a love and pride toward theinstitution.Keywords: Entrepreneurship, Independent Business, Brand, Design, UNRIYO